BUDAYA NONGKRONG ANAK MUDA DI KAFE (Tinjauan Gaya Hidup Anak Muda Di Kota Denpasar) - Fauzi, Ahmad; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT A growing number of cafes in Denpasar accompanied by hanging out (nongkrong) culture which is becoming increasingly common among young people nowdays becomes an interesting phenomenon to be analyzed. This research attempts to explain the relation between the existence of cafes with hanging out culture which are formed in terms of how young people assess the function of the exsistence of the café itself. Through the perspective of ‘consumption society theory’ and qualitative research methods, it was found that the culture of hanging out in the cafe for young people not only to enjoy a limited menu provided, but the young people as consumers were also taking space as a form of self definition that exists as efforts to establish their lifestyle. This research was conducted in three different cafes and focused on youth aged 18 to 24 years. Based on the results of research obtained that the spread of cafes in the city of Denpasar was a response to the presence of young people exsistence that loaded to meet the desires, tastes, and the establishment of their lifestyle. The café was not only become a place to hang out functionally, but also interpreted has shifted from use values that led to sign values. The café was no longer an essential place for mere physical or biological needs, but as a symbol of self-existence and lifestyle of young people in Denpasar. Keywords: cafes, hanging out culture, young people, consumption society